Nilai Perusahaan, Indeks Tata Kelola Perusahaan dan Struktur Modal - Wahyuni, Fitri (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 2 (2018), 2018)
This study aims to test the capital structure as a moderating variable of the relationship between corporate governance index and firm value. We want to see if the company has a concern for corporate stakeholders through the disclosure of the corporate governance index and also seeks to reduce conflicts within the company, such as agency conflict and information asymmetry. The corporate governance index was developed by Forum for Corporate Governance in Indonesia (FCGI) and Price Waterhouse Coopers (PwC), the value of companies in this study calculated using TobinQ and capital structure was calculated using debt to equity ratio (DER). The result shows that capital structure becomes moderation in relation between corporate governance index and firm value with negative direction. The results show that the company's concern for shareholders, the company wants to reduce the conflicts within the company. In addition, when the firm discloses the capital structure, shareholders find it insecure to invest in the company. Keywords: corporate governance index, capital structure, firm value.